2019
DOI: 10.1097/j.pain.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain is associated with a brain aging biomarker in community-dwelling older adults

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 40 publications
7
88
2
Order By: Relevance
“…Very recently, Cruz-Almeida and co-workers published a comparison of brain age delta between 33 elderly individuals with chronic pain (mean age: 70.6 ± 5.5 years) and 14 individuals without chronic pain (mean age: 71.5 ± 7.3 years). While the mean predicted brain age was smaller than the chronological brain age in both groups (p = 0.592), participants with chronic pain had a larger brain age delta after adjustment for chronological age, sex, and exercise levels (ANCOVA, F [1,41] = 4.9; p = 0.033) (35). There are major differences between Cruz-Almeida et al's study and our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Very recently, Cruz-Almeida and co-workers published a comparison of brain age delta between 33 elderly individuals with chronic pain (mean age: 70.6 ± 5.5 years) and 14 individuals without chronic pain (mean age: 71.5 ± 7.3 years). While the mean predicted brain age was smaller than the chronological brain age in both groups (p = 0.592), participants with chronic pain had a larger brain age delta after adjustment for chronological age, sex, and exercise levels (ANCOVA, F [1,41] = 4.9; p = 0.033) (35). There are major differences between Cruz-Almeida et al's study and our study.…”
Section: Discussioncontrasting
confidence: 85%
“…Community-dwelling older adults with chronic pain had lower whole-brain fractional anisotropy (Cruz-Almeida et al, 2017) and higher white matter hyperintensity burden compared to age-matched controls (Buckalew et al, 2008;Cruz-Almeida et al, 2017). Recent evidence also suggested that chronic pain was associated with added "age-like" brain atrophy in relatively healthy older individuals using whole-brain measures of gray and white matter volume (Cruz-Almeida et al, 2019), further supporting associations between pain and brain morphology in aging.…”
Section: Associations Between Susceptibility To Chronic Pain and Age-mentioning
confidence: 96%
“…On the other hand, fibromyalgia has been related to alterations in gray and white matter volume in certain areas of the brain [260]. Another study in older people has shown an association between chronic pain and brain atrophy [44].…”
Section: Functional Magnetic Resonance Imaging (Fmri) and Chronic Painmentioning
confidence: 99%
“…It should be noted that despite the lack of an objective reference for the evaluation of chronic pain, many studies have tried to induce pain levels in a controlled manner (by heat [23,[41][42][43][44][45][46][47][48][49][50][51][52][53], cold [45,48,52], pressure [44] or electrical stimulation [54]) as a first approximation to a method that allows the evaluation of chronic pain [1]. In contrast to the studies based on research with phasic pain stimuli (short duration), the number of studies based on tonic pain stimuli is growing as an approach to chronic pain [23,[41][42][43][44][45][46][47][48][49][50][51][52][52][53][54][55]. This validation approach represents an objective way for assessing chronic pain, leaving aside all the subjectivity that may be related to the perception of pain by the chronic patient [23,[41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation